PENINGKATAN KEMAMPUAN KOLABORASI SISWA KELAS VII PADA PELAJARAN INFORMATIKA MENGGUNAKAN MEDIA PERMAINAN ULAR TANGGA DENGAN MODEL KOOPERATIF TGT - Kulsum, Ummi; Muhammad Alfan; Ratna Agustyasari; Fitriyah Ningsih; M. Shokhiful Fikri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by snakes and ladders media on the collaboration skills of junior high school students in the digital era. The TGT model groups students heterogeneously and uses tournaments as a medium for healthy competition, so it is considered effective in improving collaboration skills, one of the 21st century skills that is very much needed in the world of work and social life. This study used a quantitative design with a sample of grade VII students of SMP Negeri 18 Malang who were selected by random sampling. Data on student collaboration skills were analyzed using descriptive and inferential statistics. The results showed that the average collaboration skills of students taught with the TGT model assisted by snakes and ladders media reached 78.13% (good category), and the paired sample t-test obtained a significance of 0.000 (<0.05), so it can be concluded that the TGT type cooperative learning model assisted by snakes and ladders media has a significant effect in improving students' collaboration skills.